To the threshold of power, 1922/33 : origins and dynamics of the fascist and national socialist dictatorships. - Knox, MacGregor (Cambridge University Press, 2007)
To the Threshold of Power is the first volume of a two-part work that seeks to explain the origins and dynamics of the Fascist and National Socialist dictatorships. It lays a foundation for understanding the Nazi and Fascist regimes through parallel investigations of Italian and German society, institutions, and national myths; the supreme test of the First World War; and the post-1918 struggles from which the Fascist and National Socialist movements emerged. It emphasizes two principal sources of movement: the nationalist mythology of the intellectuals and the institutional culture and agendas of the two armies, especially the Imperial German Army and its Reichswehr successor. The book's climax is the cataclysm of 1914-18 and the rise and triumph of militarily organized radical nationalist movements - Mussolini's Fasci di combattimento and Hitler's National Socialist German Workers' Party - dedicated to the perpetuation of the war and the overthrow of the post-1918 world order.